Cognitive implications of white matter microstructural changes in individuals with low heart rate variability: a NODDI study - Jiang, Shaofan; Cheng, Yingzhe; Luo, Ling; Jiang, Rifeng; Pan, Xiaodong; Xue, Yunjing (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to investigated the microstructural integrity of WM and the relationship with the cognitive domains and cognition-related plasma biomarkers in low heart rate variability (HRV).MethodsOur study recruited 44 high HRV and 44 low HRV (Grouping by median of HF). Diffusion Magnetic resonance imaging (MRI) was utilized for the calculation of neurite orientation dispersion and density imaging (NODDI) parameters, and tract-based spatial statistics (TBSS) were employed to explore differential clusters. The fibers covered by these clusters were defined as regions of interest (ROI) for the extraction of NODDI parameter values and the analysis of their correlation with cognitive domains and cognition-related plasma biomarkers.ResultsThe TBSS analysis unveiled specific cerebral regions exhibiting disparities within the low HRV group high HRV group. These differences were evident in fractional isotropy (FISO; p < 0.05). The extracted values from these ROIs (p < 0.05) were mainly manifested in the anterior regions of the brain and corpus callosum. Further analysis showed that the abnormal white matter (WM) showed significant correlations with CDR, RCFT-I, RCFT-D, attention, memory, language, and cognition-related plasma biomarkers to varying degrees.ConclusionPatients with low HRV exhibit distinctive patterns of microstructural changes in the WM as revealed by the FISO which indicate a decline in white matter integrity, and the relationship between low HRV-related and worse cognitive performance may be attributed to damage of the frontal-corpus callosum pathways.